Teori Negara Marxis - Eric Hiariej (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2003)
By offering a contradictory perspective, the article aims to review thoughts by Marx and Engels on state. The key contradictory is on the notion of state as either being a dominant social class instrument (instrumentalist view) or a relatively-autonomous institution (structuralist view). As argued by the author, the contradiction is originated from the shifting perspectives adopted by Marx and Engels. The article underlines further the background of which Marx and Engels produced their theories on state, i.e. as a response to the dominating liberal theory on state. Finally, concepts such as 'class' and 'capitalism' are also discussed in light of the need to comprehend their theory on state based on historical materialism framework.